The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2192/ursus-s-20-00004.1
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of noninvasive sampling techniques for Malayan sun bears

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Apart from targeting highly polymorphic regions of the mitochondrial genome, the primers used in this study may be effective for samples where poor DNA quality and quantity precludes whole mitogenome construction. We successfully amplified all hair and blood samples in this study, including 20 hair samples collected non-invasively from wild sun bears using the CR1 (764 bp) marker (Tee et al 2020). These markers hold much promise, therefore, for studies of genetic isolation and contemporary gene flow in sun bear populations.…”
Section: Phylogenetic and Haplotypic Network Analysis Using Bayesian And Maximum Likelihood Treesmentioning
confidence: 99%
“…Apart from targeting highly polymorphic regions of the mitochondrial genome, the primers used in this study may be effective for samples where poor DNA quality and quantity precludes whole mitogenome construction. We successfully amplified all hair and blood samples in this study, including 20 hair samples collected non-invasively from wild sun bears using the CR1 (764 bp) marker (Tee et al 2020). These markers hold much promise, therefore, for studies of genetic isolation and contemporary gene flow in sun bear populations.…”
Section: Phylogenetic and Haplotypic Network Analysis Using Bayesian And Maximum Likelihood Treesmentioning
confidence: 99%
“…Moreover, it was concluded that the camera trap was more likely to detect grizzly bears than the hair trap in the sampling sites where they both were deployed. The same situation occurred for sun bears, when the camera detected more visits than the hair trap [110].…”
Section: Noninvasive Genetics In Bear Conservation and Managementmentioning
confidence: 65%
“…A hair clump is considered a sample worth collecting when it contains a minimum of five underfur hairs on a set of barbs [37,81]. The number of hair follicles from a sample is usually positively associated with the amplification success [63,69,109,110,117,134]. The bunch of hair from one wire is usually considered an individual [78] and is kept separate from others [89].…”
Section: Hair Samples Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most forest-dwelling species of bears rub on trees and other objects, such as rocks and utility poles, a behavior thought to be a form of intraspecific communication via chemical scent-marking (Laurie and Seidensticker 1977, Karamanlidis et al 2007, Latham et al 2012, Nie et al 2012, Sato et al 2014, Tattoni et al 2015, Filipczyková et al 2017, Tee et al 2020). These rubbing behaviors often involve repeated visits to trees, such that rubs are easily identified by their smooth, discolored bark and the presence of clumps of hair and bite and claw marks (Burst and Pelton 1983).…”
mentioning
confidence: 99%